A comparison of two methods for the definition of Regional Metropolitan Areas through an application in the North of Portugal - Rui António Ramos; Antônio Nélson Silva; Vasco Miranda (European Regional Science Association (ERSA), 2004)
The objective of this paper is to present a comparison of two methods for the definition of regional metropolitan areas, in a perspective of identification of urban territories with similar characteristics. In this study it is assumed that population density is, in the absence of another measure that describe daily or weekly individual movements, a variable that can be used to evaluate, although indirectly, the activity level and dynamics of the territory. The first method explored here uses ESDA (Exploratory Spatial Data Analyses) techniques for the definition of regional metropolitan areas. The second method is based on an index value that results from a rank of the variable under analysis in a spatial context, both at the local and national (or regional) levels. The methods are implemented in a case study in the north of Portugal, where this is a very opportune issue.
Keywords: 330